Goddess Puja in California: Embodying Contemplation Through Women’s Spirituality Education - Jordan, Nané (Paideusis, 2013)
This essay conveys an embodied, relational view of contemplative practice in education through my experience of a “Goddess puja.” I undertook this puja with two other women in the context of exploring and documenting the experiences of seven faculty and student alumni, myself included, within a Women’s Spirituality Master of Arts (WSMA) degree program located in the San Francisco Bay area. I highlight a holistic, ritual scope for considering “contemplative practices,” by engaging an embodied view of contemplative practice based from Women’s Spirituality education. The practice of Goddess puja or worship is a devotional, contemplative ritual offering of flowers and substances made to the deity in order to receive her blessing. The practice of supplicating Goddess impacts my work in midwifery and my lived philosophy, where ritual contemplation evokes further learning and inquiry about the nature of birth and birth-giving.